A comparison of time-homogeneous Markov chain and Markov process multi-state models. Issue 3 (1st October 2016) - Wan, Lijie; Lou, Wenjie; Abner, Erin; Kryscio, Richard J.
ABSTRACT: Time-homogeneous Markov models are widely used tools for analyzing longitudinal data about the progression of a chronic disease over time. There are advantages to modeling the true disease progression as a discrete time stationary Markov chain. However, one limitation of this method is its inability to handle uneven follow-up assessments or skipped visits. A continuous time version of a homogeneous Markov process multi-state model could be an alternative approach. In this article, we conduct comparisons of these two methods for unevenly spaced observations. Simulations compare the performance of the two methods and two applications illustrate the results.